Employee voice and innovative work behaviour: empirical evidence from South Africa - Larysa Botha; Renier Steyn (Cogent Psychology, 2022)
Numerous empirical studies reveal that innovative work behaviour (IWB) has several antecedents, including leadership style (LS) and climate for innovation (CfI). However, literature reporting on how different types of employee voice (EV) influence IWB is scant. This research aims to empirically determine how different dimensions of EV are linked to IWB, and also to determine the relative importance of EV, compared to other predictors of IWB, namely LS and CfI. In a cross-sectional survey, respondents were asked questions on EV and IWB, as well as on CfI and the leadership styles. Reliability and validity for all measures were calculated, as well as correlation and regression analyses were used to test the bivariate and relative prediction power of the EV as an antecedent of IWB. The demographics of the 620 respondents from 11 organisations resonated well with national workplace statistics. All measures showed acceptable psychometric properties. Supportive voice and, particularly, constructive voice, positively correlated with IWB, while defensive and destructive voice had no effect on IWB. The model in which EV was used to predict IWB was superior to models that included leadership style as well as CfI. This research provides empirical evidence that EV contributes positively to IWB, depending on the type of EV expressed, and that EV, more than other often-mentioned antecedents, predicts IWB, emphasising the relative importance of EV as a predictor of IWB. Managers should monitor the EV expressed in their environment, and promote the expression of supportive voice and, particularly, constructive voice, should they aspire to foster IWB in their workplaces.